Women's empowerment on a local level in Turkey: the case of violence against women. (15th March 2019) - Sumbas, Ahu; Koyuncu, Berrin
ABSTRACT: Moving from the assumption that local governments are significant stakeholders of women's empowerment policies, this article aims to examine the struggle against violence against women (VAW) at the local level through gender-sensitive policies employed by female mayors from a gender perspective and how these can be utilized as collective transformative resources for women's empowerment. Based on a field-study, the contention of this article is that gender budgeting, gender-sensitive collective-labor contracts, and women's support centers are institutional resources for the transformation of the municipal-budget, for attitude transformation in male employees, and for sustainable empowerment policies in the struggle against VAW in municipalities in Turkey. This article, stressing the link between the struggle against VAW and women's empowerment, reveals the significance of institutionalization of gender-sensitive policies and the struggle at local level as two prominent factors taken to be into consideration in women's empowerment.